2022
DOI: 10.3390/jof8070660
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi Mediated Enhanced Biomass, Root Morphological Traits and Nutrient Uptake under Drought Stress: A Meta-Analysis

Abstract: Drought stress remains the major constraint in affecting crop productivity in several arid and semi-arid areas highlighting climate change perspectives. Arbuscular mycorrhizal fungi (AMF) belong to a versatile class of plant–fungal symbiotic associations establishing drought stress alleviation. Nevertheless, the mechanistic mode of sustainable agriculture necessitates rigorous assessment for authentic and reproducible plant growth parameters. Understanding the plant growth promotion, root morphological changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 64 publications
(98 reference statements)
2
18
0
Order By: Relevance
“…Chitarra et al (2016) [ 16 ] have also reported that AMF symbiosis increased stomatal conductance, net photosynthesis, and related parameters, showing a higher photosynthetic capacity in these plants. A meta-analysis carried out by Chandrasekaran et al [ 17 ] revealed that plants inoculated with AMF under hydric stress conditions have a significant increase in growth, being up to 49% higher; they also have an increase in the absorption of nutrients, which produces better crop yield. In plants of Robinia pseudoacacia L., the height increased by 100% with the inoculation of AMF with respect to the non-inoculated ones [ 18 ], and the growth of the seedlings of Pistacia vera L. treated with AMF was greater than that of the treatment without AMF.…”
Section: Introductionmentioning
confidence: 99%
“…Chitarra et al (2016) [ 16 ] have also reported that AMF symbiosis increased stomatal conductance, net photosynthesis, and related parameters, showing a higher photosynthetic capacity in these plants. A meta-analysis carried out by Chandrasekaran et al [ 17 ] revealed that plants inoculated with AMF under hydric stress conditions have a significant increase in growth, being up to 49% higher; they also have an increase in the absorption of nutrients, which produces better crop yield. In plants of Robinia pseudoacacia L., the height increased by 100% with the inoculation of AMF with respect to the non-inoculated ones [ 18 ], and the growth of the seedlings of Pistacia vera L. treated with AMF was greater than that of the treatment without AMF.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the concentrations of nitrogen, potassium, copper, iron, and zinc in grape fruits were improved by MT supplemental ( Xia et al., 2021 ). Mycorrhiza can obviously promote the absorption of N, P and Fe, make the seedlings more conducive to nutrient growth and alleviate the damage caused by stress to plants ( Chandrasekaran, 2022 ). In this study MT and AM both increased significantly the concentration of P in seedling leaves under watering and drought condition, importantly, which contributed to drought tolerance enhancement ( Begum et al., 2020 ; Bechtaoui et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This process has been explained as a form of plant priming that leads to a higher resistance of AM plants to different pathogens [7][8][9][10][11][12]. Plants benefit from the symbiotic association also upon drought stress: AM fungi have been shown to modulate water loss in different crops [13,14]. Similarly, ECM colonization of the root increases the plant water and nutrient supply [15], providing protection against soil pathogens [16].…”
Section: Introductionmentioning
confidence: 99%